Stress, sleep and recovery in elite soccer: A critical review of the literature - Nedelec, M.; Halson, S.; Abaïdia, A.-E.; Ahmaidi, S.; Dupont, G. (Sports Medicine, 2015)
In elite soccer, players are frequently exposed to various situations and conditions that can interfere with sleep, potentially leading to sleep deprivation. This article provides a comprehensive and critical review of the current available literature regarding the potential acute and chronic stressors (i.e. psychological, sociological and physiological stressors) placed on elite soccer players that may result in compromised sleep quantity and/or quality. Sleep is an essential part of the recovery process as it provides a number of important psychological and physiological functions. The effects of sleep disturbance on post-soccer match fatigue mechanisms and recovery time course are also described. Physiological and cognitive changes that occur when competing at night are often not conducive to sleep induction. Although the influence of high-intensity exercise performed during the night on subsequent sleep is still debated, environmental conditions (e.g. bright light in the stadium, light emanated from the screens) and behaviours related to evening soccer matches (e.g. napping, caffeine consumption, alcohol consumption) as well as engagement and arousal induced by the match may all potentially affect subsequent sleep. Apart from night soccer matches, soccer players are subjected to inconsistency in match schedules, unique team schedules and travel fatigue that may also contribute to the sleep debt. Sleep deprivation may be detrimental to the outcome of the recovery process after a match, resulting in impaired muscle glycogen repletion, impaired muscle damage repair, alterations in cognitive function and an increase in mental fatigue. The role of sleep in recovery is a complex issue, reinforcing the need for future research to estimate the quantitative and qualitative importance of sleep and to identify influencing factors. Efficient and individualised solutions are likely needed. Volltext über: https://www.researchgate.net/publication/280389239_Stress_Sleep_and_Recovery_in_Elite_Soccer_A_Critical_Review_of_the_Literature